(untitled) (XXI Century. Spanish Literature and Culture, 2017)
The space in the work of José María Merino acts as a framework for the actions of the characters and also as an agent that helps in the reflection about the identity of the protagonists. A decisive element in the creation of the characters’ daily life. However, within this everyday reality, tragic events arise over the characters affecting negatively their lives. To combat the suffering generated by the disastrous events that persecute the characters, they consider a strategy to get away from the present sorrow and try to alleviate their pain creating imaginary scenarios: getaway spaces. In view of this, it is proposed to study in this research how in Novela de Andrés Choz and El lugar sin culpa, spaces emerge helping the main characters to run away from the affliction they suffered. A study where the concept of getaway space will be defined, how it is created in the two Merino’s novels and what are the results of its implementation.